(untitled) (Praxis Educativa, 2012)
Many authors coincide in referring to the concept of society as equivalent to that of a fabric, a web that is woven by us, human beings, like threads that are tied into knots, that support each other and, in their tangling and twisting, give sense to social organization as a whole Our intertwining is produced right from the outset of the process of socialization, which in accordance with the successive identifications constructed, prefigures a "place" for us in that intricate web. together with the promise of the right for us to obtain other spaces within the permanent and dynamic remaking of that live fabric. But today, we can think about the dominance of another type of fabric, of which many of us. who think of ourselves as being included and working for the inclusion of others, may be victims or victimizers Arachne’s web - in which objects predominate over individuals and the ambition of the former and the conformism of the latter prevail over the webs of solidarity and compromise, where the meaning that the project of existence confers to life is confused with survival imperious needs, empty of all human content. Understanding the substantial difference between Athena’s inclusive web and Arachne’s paralysing one is crucial for educators who support teaching as a way of political intervention in pursuit of emancipation and social justice.